Risk of orthorexia nervosa in university students: a review (Research, Society and Development, 2022)
A balanced and healthy diet is extremely important and contributes to health promotion, so making good choices is essential to have a good quality of life and life expectancy. However, having a perfectionist and extreme view around food and the way we eat leads to illness in the body and mind. Objective: To identify studies on the risk of developing orthorexia nervosa in university students. Methodology: This study focuses on an exploratory narrative review, in which the search process was carried out in April and May 2022 in the PubMed, Scielo and Google Scholar databases, using the descriptors in Portuguese: “Orthorexia nervosa", "Eating behavior", "Students", "Food intake" and in English: "Orthorexia nervosa", "Eating behavior", "Students", "Food intake" Results: 190 studies were found on the subject, after application of exclusion criteria 8 studies were selected. Conclusion: From the analysis of data, university students, especially those in the health area, have a high prevalence for the development of orthorexia nervosa, being more frequent in females, being more susceptible due to numerous factors, including the media, the standards imposed by society and even the requirements that are imposed when choosing a course in the health area.